Problematika Penerapan Kurikulum Merdeka Belajar pada Pembelajaran Biologi di SMA Negeri 1 Waigete - Fransiska Fintelsia Dua Wuli; Dian Ernaningsih; Mariana Sada (Jurnal Pendidikan Kimia, Fisika dan Biologi, 2025)
This study aims to examine the implementation of the independent learning curriculum in biology at SMA Negeri 1 Waigete. The objectives are: (1) to describe how the independent learning curriculum is applied in biology classes; (2) to identify the challenges teachers face during its implementation; and (3) to explore the strategies employed by teachers to overcome those challenges. Using a descriptive-qualitative approach, the research collects data through interviews, observations, and documentation. Interviews were conducted with the principal, vice principal of curriculum, and biology teachers. Observations were made during the learning process in the classroom, while documentation included teaching modules and supporting articles. Data analysis was carried out in three stages: data coding, presentation, and drawing conclusions. The findings indicate that the independent learning curriculum in biology for Class X (Phase E) was implemented effectively, with teachers preparing KOSP, learning tools, and providing materials such as readings and videos. Teaching also considered local potential and involved both formative and summative assessments. However, several problems were identified, including limited facilities and infrastructure, lack of internet access, insufficient training, and some students lacking personal devices. Moreover, teachers experienced difficulty in selecting appropriate learning strategies to engage students effectively. To address these issues, teachers have participated in curriculum-related training and prepared printed materials and pre-downloaded videos for students without digital access. These efforts show a proactive approach to ensuring all students can benefit from the independent learning curriculum despite existing limitations.